Fisiologia e controle do ciclo estral em fêmeas de cateto (tayassu tajacu, Linnaeus, 1758)) mantidas em cativeiro no semi-árido brasileiro - Maia, Keilla Moreira (Universidade Federal Rural do Semi-Árido, 2011)
The aim of this research was to study the estrous cycle physiology of female collared peccaries bred in captivity at Semiarid. At the first experiment, the changes in hormonal status (estrogen and progesterone), vaginal cytology and ovarian ultrasonographic patterns were described and correlated in four mature females. It was monitored 1.5 estrous cycle per animals during 45 days evaluation, with an average duration of 21 ± 5.7 days, estrogen presented a peak value of 55,57 ± 20,47 pg/mL and during the luteal phase, the peak values for progesterone were 35.3 ± 4.4 ng/mL. The diameter of the ovarian follicles was 0.23 ± 0.1 cm during the moment of the estrogen peak and corpora lutea measured 0.36 ± 0.2 cm identified during the luteal phase, through ultrasound evaluation. No relations amongst the hormonal profiles and vaginal cytology were identified during any moment of the cycle (P > 0.05), it was suggested that the second method was not accurate for estrus monitoring in the above mentioned species. In the second experiment, we tested a protocol for synchronization of estrus in five female collared peccaries, using two doses of 0.8 mL (60 μg) of the prostaglandin analogue, cloprostenol, with an interval of nine days, performing alongside the dosage of estrogen to monitor the estrous cycle. The occurrence of estrogen peak was verified in all the animals after the second application at 9.2 ± 1.1 days, with an average of 28.05 ± 10.41 pg / ml estrogen, and the external signs of estrus, as opening vulvar, vaginal mucosa hyperemic and vaginal mucus were observed in four animals (80%). Therefore, it was proved the efficiency of the application of a prostaglandin analogue, cloprostenol, on estrus synchronization in this species.
Physiology and control of estrous cycle in female collared peccary (Tayassu tajacu, Linnaeus, 1758)) kept in captivity in semi-arid region
Keywords: collared peccary; hormonal profile; vaginal cytology; ovarian ultrasonography; oestrus synchronization; cateto; perfil hormonal; citologia vaginal; ultrassonografia ovariana; sincronização de estro; CIENCIAS AGRARIAS::MEDICINA VETERINARIA